Analisis Kegiatan Serta Pemenuhan Kebutuhan Lansia - Ramadhan Lubis; Zhafira Nur ‘Ulya Alsa; Maulida Apriani Nasution; Alfiani Maulida; Abrar Azizi; Aisyah Alya (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to analyze the daily activities of older adults and the fulfillment of their needs through a case study of Mrs. Zuriatimaida, a 63-year-old elderly woman who remains active and independent. Data were collected through in-depth interviews examining physical, cognitive, psychomotor, social, emotional, spiritual, and economic aspects. The findings show that she maintains a productive lifestyle through activities such as running a small catering business, managing boarding rooms, participating in social gatherings (such as religious study groups and elderly health posts), and maintaining regular religious practices. Her physical condition is generally good, cognitive function remains stable, and psychomotor abilities support daily independence. Positive social interactions, strong spiritual commitment, and financial stability contribute significantly to meeting both her physical and psychological needs. These findings align with biological and psychosocial aging theories, activity theory, emotional regulation theory, and cognitive functioning theory, which emphasize the role of social engagement, mental stimulation, and spiritual well-being in later life. Overall, the study concludes that structured activities, supportive social environments, and emotional-spiritual balance play essential roles in sustaining the well being of older adults.